2022
DOI: 10.31557/apjcp.2022.23.8.2771
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Cervical Cancer Screening among Reproductive Age Group Women: Evidence from Cross-Sectional Study in Rohtak and Delhi

Abstract: Background:The present study aims to estimate the prevalence and determine the factors for cervical cancer screening among women in the reproductive age group in Delhi and Rohtak, India. Methods: The data were utilized from a survey conducted as part of a larger study to increase the access to cervical cancer screening and care by MAMTA-Health Institute for Mother and Child in collaboration with the Health Departments of Palam, New Delhi, and Rohtak, Haryana between 2015 and 2017. Data pertaining to the socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…When compared to other countries, the cervical cancer screening rate in Saudi Arabia based on this study was found to be lower than the rates in Jamaica (40.7%) [ 35 ], China (63.7%) [ 36 ], Georgia (67%) [ 37 ], the United Kingdom (72%) [ 38 ], Brazil (73%) [ 37 ], Austria (80%) [ 37 ], and the United States (93%) [ 39 ]. However, the rate of cervical cancer screening among Saudi women in this study (22.1%) was higher when compared to Ethiopia (17.8%) [ 40 ], Nepal (15.7%) [ 41 ], Ghana (12%) [ 42 ], Uganda (4.8%) [ 43 ], India (3.9%) [ 44 ], and Cameroon (3.5%) [ 45 ]. Rates similar to those found in this study were found in Tanzania (21%) [ 46 ] and Turkey (21.9%) [ 47 ].…”
Section: Discussionmentioning
confidence: 84%
“…When compared to other countries, the cervical cancer screening rate in Saudi Arabia based on this study was found to be lower than the rates in Jamaica (40.7%) [ 35 ], China (63.7%) [ 36 ], Georgia (67%) [ 37 ], the United Kingdom (72%) [ 38 ], Brazil (73%) [ 37 ], Austria (80%) [ 37 ], and the United States (93%) [ 39 ]. However, the rate of cervical cancer screening among Saudi women in this study (22.1%) was higher when compared to Ethiopia (17.8%) [ 40 ], Nepal (15.7%) [ 41 ], Ghana (12%) [ 42 ], Uganda (4.8%) [ 43 ], India (3.9%) [ 44 ], and Cameroon (3.5%) [ 45 ]. Rates similar to those found in this study were found in Tanzania (21%) [ 46 ] and Turkey (21.9%) [ 47 ].…”
Section: Discussionmentioning
confidence: 84%
“…This observation is in line with the research conducted by Srivatsa et al, which suggests that women hailing from households with a higher income are significantly more inclined to undergo cervical cancer screening compared to those from lower-income households. 20,21 Additional studies such as Kaneko, 2018, and Keetile et al, 2021 have similarly argued that disadvantaged households are often less informed and thus less likely to prioritize cervical cancer screening. 22,23 A notable finding underlines the influence of travel-related variables on overall expenses.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HPV infection has shown to vary by region, country and, within a country, by population sub-groups [13] [14] [15]. Type-specific distri-bution of HPV infection also varies by geographic region [16] [17] [18] [19] [20].…”
Section: Introductionmentioning
confidence: 99%